2022
DOI: 10.1021/acsanm.2c02166
|View full text |Cite
|
Sign up to set email alerts
|

Giant Carrier Mobility in Graphene with Enhanced Shubnikov–de Haas Quantum Oscillations: Implications for Low-Power-Consumption Device Applications

Abstract: Graphene devices are susceptible to the surrounding environment. For example, the substrate in contact with graphene influences the device performance because the carriers are confined in two-dimensional (2D) atomic thickness. However, 2D van der Waals dielectric materials used as an interface modifier can provide a path to improve the device quality. In this paper, we report enhanced mobility of up to 540 000 cm 2 V −1 s −1 in monolayer graphene sandwiched between two layers of a CrOCl insulator through a die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Bolotin et al also reported its mobility is larger than 17 m 2 V −1 s −1 in ultraclean suspended graphene at 5 K [40]. Moreover, by reducing the Coulomb interaction between electrons and charged impurities, they can substantially enhance the mobility of graphene up to 54 m 2 V −1 s −1 in monolayer graphene sandwiched between two layers of a CrOCl insulator [41]. Due to its ability to be efficiently controlled by the Fermi level and carrier mobility, graphene has the much potential applications in optical and optoelectronic devices [42].…”
Section: Design and Simulationmentioning
confidence: 97%
“…Bolotin et al also reported its mobility is larger than 17 m 2 V −1 s −1 in ultraclean suspended graphene at 5 K [40]. Moreover, by reducing the Coulomb interaction between electrons and charged impurities, they can substantially enhance the mobility of graphene up to 54 m 2 V −1 s −1 in monolayer graphene sandwiched between two layers of a CrOCl insulator [41]. Due to its ability to be efficiently controlled by the Fermi level and carrier mobility, graphene has the much potential applications in optical and optoelectronic devices [42].…”
Section: Design and Simulationmentioning
confidence: 97%
“…2) In general, reduced GOs (r-GOs) have poorer electrical properties compared with ideal graphene. 3) Therefore, various reduction methods of hightemperature annealing, [4][5][6] chemical treatments using hydrazine, 7) and green reductants 8) have been investigated to obtain excellent electrical properties. In general, the electrical properties of graphene transferred from a Cu substrate onto a SiO 2 dielectric film are degraded by graphene wrinkles 9) and an SiO 2 underlayer.…”
Section: Introductionmentioning
confidence: 99%
“…Transport properties serve as a crucial tool to understand the scattering mechanisms in the two-dimensional electron gas (2DEG) channel effectively. Various characterization techniques have been employed to ensure the production of high-quality samples. Magnetoresistance measurements in quantum transport serve as a powerful tool for characterizing compound semiconductors, facilitating a deeper understanding of their electronic properties. Quantum oscillations and their scattering phenomena have been extensively explored in various GaN based heterostructures. ,, However, the quantum transport behaviors in this high-mobility InAlN/GaN heterostructure have not been widely reported. In particular, study on the InAlN/GaN 2DEG systems with high mobility remains a long-standing challenge due to growth challenges.…”
Section: Introductionmentioning
confidence: 99%